2022
DOI: 10.4251/wjgo.v14.i2.434
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal treatment in oligometastatic gastric cancer

Abstract: Gastric cancer is generally diagnosed at an advanced stage, especially in countries without screening programs. Previously, the metastatic stage was synonymous with palliative management, and surgical indications were only for symptomatic relief. However, this therapeutic option is associated with poor prognosis. A subgroup of patients with limited metastatic disease could benefit from intensive treatment. A combination of chemotherapy, immunotherapy, and targeted therapy could help either maintain a resectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that radical resection could bene t highly selected oligometastatic gastric cancer patients [29,30]. Indeed, it has been reported that PFS of 25.5 months reached in 13 patients with metastatic disease (P1 or CY1) who achieved P0 or CY0 after chemotherapy and underwent R0 gastrectomy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that radical resection could bene t highly selected oligometastatic gastric cancer patients [29,30]. Indeed, it has been reported that PFS of 25.5 months reached in 13 patients with metastatic disease (P1 or CY1) who achieved P0 or CY0 after chemotherapy and underwent R0 gastrectomy [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that radical resection could benefit highly selected oligometastatic gastric cancer patients [ 29 , 30 ]. Indeed, it has been reported that PFS of 25.5 months reached in 13 patients with metastatic disease (P1 or CY1) who achieved P0 or CY0 after chemotherapy and underwent R0 gastrectomy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…treatment for cancer experiences a recurrence in a limited number of locations in the body [11]. Appropriate localized treatment could prolong survival in selected patients [12], while treatment consensus for oligorecurrence of gastric cancer has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…The present case was considered as repeat oligorecurrence, which refers to a situation where a cancer patient who has previously undergone treatment for cancer experiences a recurrence in a limited number of locations in the body [ 11 ]. Appropriate localized treatment could prolong survival in selected patients [ 12 ], while treatment consensus for oligorecurrence of gastric cancer has not been established.…”
Section: Discussionmentioning
confidence: 99%